Effective dual-mode fuzzy DMC algorithms with on-line quadratic optimization and guaranteed stability - Marusak, Piotr M.; Tatjewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Dual-mode fuzzy dynamic matrix control (fuzzy DMC-FDMC) algorithms with guaranteed nominal stability for constrained nonlinear plants are presented. The algorithms join the advantages of fuzzy Takagi-Sugeno modeling and the predictive dual-mode approach in a computationally efficient version.
Keywords: nonlinear systems; fuzzy systems; model predictive control; stability; constrained control; dual-mode control